2016
DOI: 10.1111/eci.12576
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of endothelin and copeptin as biomarkers for vasovagal syncope

Abstract: Circulating plasma endothelin-1 and copeptin levels are not significantly different among populations of controls, syncope patients and seizure patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…To minimize this confounder, all participants ingested 1 L of water the night before the experiments. We found no link between copeptin and number of or frequency of syncopal events, in correspondence with recent work . Lastly, we present novel correlations between copeptin level and size of both the RV and the LA, reflecting its close bond with central blood volume, indicating a “reserve preload capacity” in controls.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To minimize this confounder, all participants ingested 1 L of water the night before the experiments. We found no link between copeptin and number of or frequency of syncopal events, in correspondence with recent work . Lastly, we present novel correlations between copeptin level and size of both the RV and the LA, reflecting its close bond with central blood volume, indicating a “reserve preload capacity” in controls.…”
Section: Discussionsupporting
confidence: 90%
“…Biomarkers have predominantly been used as a diagnostic tool to identify syncope subject, 8,13 or to distinguish between syncope subgroups, 7,9,10,12 while a minority of studies have tried to explore the relationship between biomarkers and pathophysiological aspects of VVS. 7,10,11 The various biomarkers were predominately measured only at rest and presented results have been partially inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, Fitzpatrick et al ( 10), Jardine et al ( 14) and Torabi et al (22) observed moderately increased AVP values early in HUT in VVS prone patients suggesting a potential marker of susceptibility, but others did not detect baseline differences (28,29,31). Nonetheless, all confirmed that AVP increased abruptly in close proximity to the faint itself.…”
Section: Vasopressinmentioning
confidence: 90%
“…However, at the time of syncope, AVP was 20-fold higher than baseline (28). On the other hand, Rash et al (29) did not observe any evident baseline AVP differences among 3 groups of patients (VVS, epilepsy and controls) but they did not provide measures during or in proximity to syncope events. Finally, Nilsson et al (30) found AVP to be higher in patients who fainted spontaneously during HUT compared to those who fainted after nitroglycerine stimulation.…”
Section: Vasopressinmentioning
confidence: 91%